Analisis Antioksidan Ekstrak Etil Asetat Dari Kulit Buah Rambutan (Nephelium Lappaceum) dengan Menggunakan Metode dpph (1,1 difenil-2-pikrilhidrakzil) - Nurfadillah, Nurfadillah; Chadijah, St; Rustiah, Waode (Al-Kimia, 2016)
Rapiah rambutan fruit leather (Nephelium lappaceum) is one of the traditional medicine to cure various diseases such as fever and dysentery. Scientific research previously stated rambutan fruit peel skin Rapiah rambutan (Nephelium lappaceum) potentially have antioxidant content. Through this research can know the effect of solvent ethyl acetate to extract optimal rambutan fruit skin in antioxidants withdrawal. The method used for extraction is macerated using methanol and partitioned with liquid-liquid extraction using ethyl acetate solvent with a ratio (1:3), (1:4) and (1:5) which produces a thick rind extract rambutan. The extract was tested color and separated by thin layer chromatography (TLC) using the eluent butanol: glacial acetic acid: water (BAA) (4: 1: 5). Antioxidants are determined by testing against DPPH free radicals by measuring the absorbance of DPPH (1,1-diphenyl-2-pikrilhidraksil) at a wavelength of 517 nm. So that the results of this study showed the highest % reduction obtained at a ratio (1:3).